2006
DOI: 10.1159/000090103
|View full text |Cite
|
Sign up to set email alerts
|

Lack of in vitro Genotoxicity of Povidone-Iodine in Solution, in Ointment or in a Liposomal Formulation (Repithel<sup>®</sup>)

Abstract: The in vitro genotoxicity of povidone-iodine in Repithel®, Betaisodona® ointment and Betaisodona® solution was investigated using CHO-K1 cells. The comet assay and chromosome aberration test were used to characterise the genotoxic potency of povidone-iodine within 4 h of contact with test cells. Methyl methanesulphonate without S9 activation and benzo[a]pyrene with S9 activation were used as positive controls. No higher concentrations than 6% Repithel, 5% Betaisodona ointment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In accordance with this, in histological tests, no tissue damage was observed in the treatment of chronic exudative wounds [167]. There is no evidence of neurotoxicity, mutagenicity, carcinogenicity, or teratogenicity [156,168]. In the cell culture (fibroblasts), 0.45% C-I was found to be noncytotoxic [167].…”
Section: Iodophorementioning
confidence: 90%
“…In accordance with this, in histological tests, no tissue damage was observed in the treatment of chronic exudative wounds [167]. There is no evidence of neurotoxicity, mutagenicity, carcinogenicity, or teratogenicity [156,168]. In the cell culture (fibroblasts), 0.45% C-I was found to be noncytotoxic [167].…”
Section: Iodophorementioning
confidence: 90%
“…1 The Panel reviewed newly available studies since that assessment, along with updated information regarding types and concentration of use. 2 26 The Panel confirmed that PVP is safe as a cosmetic ingredient in the practices of use and concentration as given in Table 1 and did not reopen the safety assessment.…”
Section: Resultsmentioning
confidence: 91%
“…At concentrations of 10% Repithel®, 5% Betaisodona® ointment and 2.5% Betaisodona® solution in culture medium (60% cytotoxicity within 4 h of contact with CHO-K1 cells), no significant increase in the CA levels compared with negative control was observed. Hence, all tested concentrations of povidone-iodine formulations were not genotoxic in the CA test and the comet assay (34). The cytotoxicity of iodine-containing drugs was relatively low -after 30 min contact time using vital dye neutral red, the following IC 50 were determined: 16-18% Repithel®, 8-9% Betaisodona® ointment and 1.8-2% Betaisodona® solution (35).…”
Section: Genotoxicity Of Iodine and The Compounds Containing Iodinementioning
confidence: 88%